Performance analysis of electrical environmental control and ice protection systems in a commercial transport aircraft - Ercan, Hamdi; Ozturk, Cuneyt; Akin, Mustafa (Emerald Group Publishing Ltd, 2024)
PurposeThis paper aims to assess the impact of electrifying the environmental control system (ECS) and ice protection system (IPS), the primary pneumatic system consumers in a conventional commercial transport aircraft, on aircraft weight, range, and fuel consumption.Design/methodology/approachThe case study was carried out on Airbus A321-200 aircraft. Design, modelling and analysis processes were carried out on Pacelab SysArc software. Conventional and electrical ECS and IPS architectures were modelled and analysed considering different temperature profiles.FindingsThe simulation results have shown that the aircraft model with +/- 270 VDC ECS and IPS architecture is lighter, has a more extended range and has less relative fuel consumption. In addition, the simulation results showed that the maximum range and relative fuel economy of all three aircraft models increased slightly as the temperature increased.Practical implicationsConsidering the findings in this paper, it is seen that the electrification of the conventional pneumatic system in aircraft has positive contributions in terms of weight, power consumption and fuel consumption.Social implicationsThe positive contributions in terms of weight, power consumption and fuel consumption in aircraft will be direct environmental and economic contributions.Originality/valueApart from the conventional ECS and IPS of the aircraft, two electrical architectures, 230 VAC and +/- 270 VDC, were modelled and analysed. To see the effects of the three models created in different temperature profiles, analyses were done for cold day, ISA standard day and hot day temperature profiles.
Keywords: More electric aircraft (MEA); Aircraft subsystem electrification; Environmental control system (ECS); Ice protection systems (IPS)